A Method to Determine the Characteristic of Naturally Fractured Reservoir Using the Integration of Core, Log, and Well Test Data - (NIM 12204006), ILFI
Naturally fractured reservoir has already known as the source of hydrocarbon reserve in the world for a long time. Because this type of reservoir has distinctive characteristics or properties which are different from homogeneous reservoir, so certain method, which is more complex, is needed to identify this reservoir. In addition, fractures can have a positive or a negative effect on fluid flow; hence they can affect the recovery of oil and gas which can be produced. So it is very important to determine the characteristics of naturally fractured reservoir. Some methods or data sources to characterize a reservoir are by using core data, log, and well test analysis. However, the presence of fractures is very difficult to detect using core data analysis, which can only determine permeability and porosity of matrix. Log data can deliver few parameters of fractures (porosity and fracture intensity), as well as well test analysis that can calculate certain properties of fracture (storativity ratio and interporosity flow parameter). This paper attempts to give a method to determine more characteristics of fractures, and also to consider the connection between one property and the others. Furthermore, dissemination of these properties in a naturally fractured reservoir can be established. The additional characteristics are fracture permeability, fracture compressibility, and fracture spacing. This method is made from the integration of three data sources above, which relates property from one data source analysis with property from the others.